2012
DOI: 10.1002/jlcr.2976
|View full text |Cite
|
Sign up to set email alerts
|

Application of LC/MS to determine specific activity variation in a series of sulfonamide tracers from the [35S]methane sulfonate reagent

Abstract: The specific activities for a series of S‐35 tracers were found to vary from the decay‐corrected specific activity of the labeled reagent. If not known before the stock solution preparation and binding assay, this variation would have resulted in performing the assay at approximately two to three times over the targeted concentration, thereby leading to considerable error in the calculated binding and related conclusions. Copyright © 2012 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(12 reference statements)
2
1
0
Order By: Relevance
“…At the higher specific activities (~120 and 61 mCi/mol, entry 1, 2) the MS‐based values from using either the unlabeled or the [ 14 C 5 ] correction patterns were similar and were less than 10% different from the UV‐based values. This level of error is consistent with past investigations . With decreasing specific activity, there was a steadily increasing difference between the UV‐based specific activity values and both series of MS‐based values with the MS‐based values calculated from the unlabeled carbamazepine pattern always being the furthest from the UV‐based values.…”
Section: Resultssupporting
confidence: 91%
“…At the higher specific activities (~120 and 61 mCi/mol, entry 1, 2) the MS‐based values from using either the unlabeled or the [ 14 C 5 ] correction patterns were similar and were less than 10% different from the UV‐based values. This level of error is consistent with past investigations . With decreasing specific activity, there was a steadily increasing difference between the UV‐based specific activity values and both series of MS‐based values with the MS‐based values calculated from the unlabeled carbamazepine pattern always being the furthest from the UV‐based values.…”
Section: Resultssupporting
confidence: 91%
“…While the accuracy range of LC/MS SA determination has not been studied exhaustively, it has been demonstrated that the method error is roughly ~6–10%, and that the specific activity and elemental composition of the tracer has a significant effect on the measurement accuracy . The current study provides a similar error range (<10%) for the NMR SA method.…”
Section: Discussion Of Resultssupporting
confidence: 69%
“…Merck tritiated tracer, [ 3 H]compound A , and [1‐methyl, C 3 H 3 ]caffeine (ViTrax Co, Placentia CA, 19.8 Ci/mmol) were used as internal standards. Radiochemical purity (Agilent 1100 series HPLC, Agilent; Radiomatic 625TR, PerkinElmer), LC/MS‐derived specific activity (Agilent MSD) and radioactive solution count (TRI‐CARB 3100TR, PerkinElmer) for each were measured. Radio‐HPLC screening using six columns provided additional confidence that compound A 19 was radiochemically pure.…”
Section: Methodsmentioning
confidence: 99%